Fabrication stacking faults and its influence on the delamination behavior of SuperPower (SCS4050®) tapes. (September 2020) - Mbam, Stephen Ogbonna; Gou, Xiao-Fan
Highlights: Stacking faults in SuperPower tapes were studied by the displacement energy approach. Stacking faults in the tape emanate from inter-layer interactions during films deposition; -Stacking faults distribution in the tape affects its delamination behaviour. 80% of the stacking faults are located around the yttrium barium copper oxide interfaces. Abstract: In this study, the authors investigated the evolution of the stacking faults (local defects) during film deposition and its influence on the delamination behavior (mechanisms) of SuperPower (SCS4050®) tapes using the DEM approach. The DEM approach was developed explicitly for the characterization of the evolution of the local defect in multilayered film structures. According to the study, major local defects in a multilayered film structure emerge from interlayer interactions as a function of temperature and time during the deposition of films unto the substrate. The interlayer interactions include the thermal coefficient of expansion mismatch and different eigenstates of layers in the tape. Also, the influence of the major film deposition methods (chemical and physical vapor deposition methods) on the evolution of the stacking faults in the tape was investigated. Under the given parameters, the results showed that the most vulnerable to the evolution of the local defects in the SuperPower (SCS4050®) tapes are the yttrium barium copper oxide (YBCO) interfaces and silver (Ag) layer. A comparison of the computed loss of bonding energy in the tape shows that, if a delamination test is carried out on the tape, above 80% of the delamination would occur around YBCO interfaces. Also, according to the stacking faults distribution with different film deposition method, it is practicable to minimize or localize stacking faults to a particular region of the tape. According to this study and previous studies, the computed results on the DEM approach are consistent with those on several valuable experiments and models in the literature.